UV‐activated hydrosilation reaction for silicone polymer crosslinking. Issue 3 (25th July 2012) - Sangermano, M.; Marchi, S.; Meier, P.; Kornmann, X.
Abstract: In this article hydrosilation was employed to achieve a fully cured three‐dimensional silicone network. The UV‐activated hydrosilation reaction was investigated focusing on the curing conditions and their relationships to physical properties. After finding the optimum catalyst concentration, it was observed that by decreasing the molecular weight of the vinyl oligomer a slight increase of the T g value was achieved together with a complete suppression of the Tm. It was possible to fully cure samples up to 4 cm of thickness. The dark curing process was evaluated by FTIR analyses and it was evidenced an important increase on dark‐polymerization, which is dependent on the length of the UV‐irradiation time. This result shows the versatility of UV‐curing technique for silicone network formation. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :